Pengembangan Lintasan Pahat Pada Pengefraisan “Umsu” Menggunakan Cnc Tu-3a - Rahmatullah Rahmatullah; Khairul Umurani; Munawar Alfansury Siregar (Fakultas Teknik UMSU, 2021)
Computer numerically controlled (CNC) machines have long been known and used in various industrial sectors such as the aircraft, shipping, automotive, molding and others industries. Various types of existing CNC machines such as CNC turning, CNC milling, CNC shaping, CNC drilling, CNC laser cutting and others have been commonly used in various manufacturing industries. CNC machines for production units and training unit CNC machines can be used according to milling machining parameters, machine capacity, product quality targets and workpiece material types. In milling machining using a 3-A training unit CNC machine, the first step is to design a workpiece, design G and M codes, simulate it using software such as CAD / CAM and can also be done by simulating it with a pen plotter. After evaluating and the simulation results are in accordance with the workpiece design, it can be executed for product machining. Different designs of CNC machining products have different toolpaths. In general, there are three types of techniques for path generation tools, namely iso-parametric, iso-planner, and iso-scallop height. Tool path generation on